Validación del método de proteína total en productos alimenticios (chifles, pan de almidón y chorizos) en el laboratorio CESECCA - Anchundia Vega, Arleth Alejandra (2023)
The purpose of this research was to validate the total protein method in food products such as: chifles (low range), starch bread (medium range) and chorizos (high range). A situational diagnosis was made in the physicochemical area of the laboratory by means of a checklist according to INEN-ISO 17025 standard to verify if it complies in the development of analysis with respect to the regulations, then the validation objectives that must be met prior to validation were raised, the protein analysis was performed by executing 200 analyses including blanks during 5 running days, with respect to the quantification of protein data were collected from the three established ranges ranging from 0.82% to 1.34%; 6.05% to 6.54% and 11.41% to 12.98% for the aforementioned matrices. By means of the analysis of variance, the homogeneity of the samples of each matrix between and within groups was measured based on the repeatability and reproducibility limits, since the F calculated for each matrix is less than the critical value for F, whose value is 2.12402. On the other hand, a matrix effect was calculated by means of the t student test to measure the probability that exists between matrices, giving as a result that there is similarity between each one of them. Finally, the uncertainty was determined by means of an Ishikawa diagram where all the contributions inherent to the method of each matrix were considered, giving a result lower than the validation objective, which must be less than or equal to 25%.